Evaluation Report on Second Year's Working of Community Projects Volume I - Planning Commission (Planning Commission, 1955)
The purpose of evaluation is to keep all concerned currently informed about the progress of the programmes of Community Projects/ the detailed operational and financial reporting on the activities of the several organizations concerned with the direction of this activity is done by the respective administrations as a normal routine. The Evaluation Report is concerned with indicating the broad trends of progress, and to appraise the several tendencies revealed by current experience. for this purpose the Evaluation Organization has to depend primarily on reports of current and special inquiries conducted through its representatives stationed in over twenty places, and on the results of observations and consultations held by its officers with several people in all parts of the country.
Planning Commission, Programme Evaluation Organisation, Government of India